Approximating the Sum of Infinite Series of Non Negative Terms with reference to Integral Test - Paudyal, Daya Ram (The Nepali Mathematical Sciences Report, 2020)
This paper describes a method of obtaining approximate sum of infinite series of positive terms by using integrals under its historical background. It has shown the application of improper integrals to determine whether the given innate series is convergent or divergent. Here, the limits of the integrals and the series usually extend to infinity though they may be slowly convergent. We have also established a relation to approximate the sum of infinite series of positive terms with a suitable example.